БИОСЕНСОРЛАРДЫҢ ЭЛЕКТРОХИМИЯЛЫҚ ҚАСИЕТТЕРІНІҢ МЫРЫШ ОКСИДІ ҚАБАТТАРЫНЫҢ МОРФОЛОГИЯСЫНА ТӘУЕЛДІЛІГІ - Gritsenko, L.V.; Tolubayeva, D.B. (Хабаршы. Физика сериясы, 2022)
Diabetes mellitus, associated with insulin deficiency and high blood glucose, is one of the leading causes of death and disability in the world. Continuous monitoring of blood glucose levels can help prevent heart disease, kidney failure, or blindness. In this regard, fast, pricese and economical identification of blood glucose levels is necessary. Therefore, the manufacture of an economical, easy-to-use, exact, portable and fast glucose biosensor is of critical importance in diabetes mellitus. Electrochemical biosensors for glucose identification are widely used. In this work, arrays of highly oriented ZnO nanorods synthesized by a low-cost method of chemical deposition from solution was used as an amperometric enzymatic electrode in which glucose oxidase (GOx) was immobilized by physical adsorption. The morphology, optical and electrochemical properties of the fabricated modified ITO/ZnO/GOx/Nafion electrode were studied. The influence of the morphology of zinc oxide layers on the activity of the enzyme and biosensor was investigated. The resulting modified ITO/ZnO/GOx/Nafion electrodes with arrays of ordered thin ZnO nanorods showed a high sensitivity of ~50 μA/mM·cm2 for the detection of glucose in solution, i.e. ZnO nanorods with a high specific surface area are an excellent platform for the immobilization of glucose oxidase in biosensors.